Implementasi Manajemen Sarana dan Prasarana Pendidikan di Sekolah Menengah Pertama - Daffa Arif Maulana Adhary; Haula Dzakiyya Rahma; Vannia Thirza Awwalia; Zahrotul Munawwaroh (Lembaga Pengembangan Kinerja Dosen, 2026)
This article discusses the implementation of educational facilities and infrastructure management at the junior high school level and its implications for the learning process. The study was conducted using a descriptive qualitative approach through a literature review, analyzing various relevant references in the form of journal articles, books, and regulations related to facilities and infrastructure standards. The discussion focused on the stages of management, including planning, procurement, inventory, utilization and maintenance, disposal, as well as supervision and evaluation. The synthesis results show that effective implementation is supported by planning based on learning needs, orderly asset administration, and routine maintenance to ensure that facilities remain suitable and ready for use. Common obstacles include budget constraints, inadequate or outdated facilities, and limited human resources and technical competence in infrastructure management. Meanwhile, supporting factors include the commitment of school leaders, collaboration between school members and committees, effective communication, and discipline in management procedures. In general, good infrastructure management has implications for increased learning comfort, support for ICT integration, strengthening of library services, and the creation of a more conducive learning environment.